Hippocampal and prefrontal atrophy in patients with early non-demented Parkinson's disease is related to cognitive impairment. Issue 10 (16th September 2004) - Brück, A; Kurki, T; Kaasinen, V; Vahlberg, T; Rinne, J O
Abstract : Background: Early stage patients with Parkinson's disease (PD) show cognitive impairment in frontal lobe functions and memory tests. Hippocampal atrophy is seen in medicated patients with advanced PD. Objectives: To examine whether prefrontal or hippocampal atrophy are already present in early stage PD, and whether such atrophy is associated with cognitive impairment. Methods: Twenty non-medicated, non-demented patients with early stage PD and 22 neurologically healthy age matched controls were studied. All subjects underwent magnetic resonance imaging to study hippocampal and prefrontal atrophy. Atrophy was evaluated by a neuroradiologist using a five point scale. In addition, the patients underwent a neuropsychological test battery sensitive to frontal lobe functions and memory. Results: Patients with PD had atrophy in the right and the left prefrontal cortex. In the right hippocampus, the mean atrophy score was 1.15 in PD and 0.45 in controls. Corresponding figures for the left hippocampus were 1.05 for PD and 0.64 for controls. In PD, the left hippocampus atrophy correlated with verbal memory and prefrontal atrophy correlated with impaired performance in a test measuring vigilance. Conclusions: Non-medicated, non-demented patients with early stage PD show hippocampal and prefrontal atrophy. Impaired memory is related to hippocampal atrophy, whereas sustained attention is related to prefrontal atrophy.